EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF NUMBERED HEADS TOGETHER (NHT) WITH THINK PAIR SHARE (TPS) TYPE TOWARDS MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII IN SMP NEGERI 2 SLEMAN - Sri Kurniawati; Uswatun Khasanah (Universitas Ahmad Dahlan, 2017)
The teacher-centered learning process makes the students less active and does not dare to express their opinion. It affects the result of students' mathematics learning. This research aims to determine the effectiveness of cooperative learning model NHT and TPS type compared with the Direct Learning type toward the result of students' mathematics learning. The type of study in this research is experimental research. The population of the research is all students in grade VIII SMP Negeri 2 Sleman in the academic year 2015/2016. The purposive sampling is used as a sampling technique, derived class VIII C as the experimental class I, class VIII D as the experimental class II and class VIII A as the control class. The data collection technique is documentation and tests. The instrument used is the test question of mathematics learning results. The prerequisite test analysis is the normality test and homogeneity test. Data analysis for hypothesis testing uses the F test continued Newman-Keuls Test Range. Research result with a significance level of and shows (1) There are differences in mathematics learning outcomes of students using cooperative learning model NHT, SMT type and the type of Learning Direct and to and (2) the results of students learning mathematics using cooperative learning model NHT and TPS type is better than the results of students' mathematics learning that uses the type of Direct Learning. It is indicated by the results of the Newman-Keuls Test Range that is the case I and then so acceptable means . In case II and then so rejected and ( then means . Whereas in the case of III and then so rejected and then means . So .